Is There a Relationship Between Paratracheal Air Cysts and Upper Lobe Fibrosis?. Issue 2 (March 2016) - Unlu, Elif Nisa; Balbay, Ege Gulec; Boran, Mertay; Sungur, Mehmet Ali; Buyukkaya, Ayla; Safak, Alp Alper
Abstract : Objective: The purpose of this study was to determine the characteristics of paratracheal air cysts (PACs) and their relationship with upper lobe pulmonary fibrosis. Materials and Methods: The routine thoracic computed tomography scans of 3549 patients carried out between January 2014 and April 2015 were retrospectively evaluated. The presence, location, structural characteristics (uniloculated or multiloculated), number of cysts, and anterior-posterior and transverse dimensions of the PAC and its communication with the tracheal lumen were evaluated. The presence of upper lobe fibrosis, emphysema, and bronchiectasis was also evaluated. The relationship between upper lobe fibrosis, emphysema, bronchiectasis, and the presence of paratracheal cysts was evaluated in all patients. An equal number of randomized patients with no paratracheal cysts were selected as a control group. Results: A total of 190 PAC cases were diagnosed, with a prevalence rate of 5.35%: 146 (76.8%) of the cases were men, 44 (23.2%) were female, and the mean (SD) age was 53.79 (16.64) years (range, 12–89 years). The control group included 105 men (57.4%) and 78 women (42.6%), and the mean (SD) age was 53.87 (16.65) years (range, 13–87 years). The groups were similar in terms of age ( P = 0.876), whereas the proportion of men in the PAC group was significantly higher ( P < 0.001). Most of the PACs were located on the right side (n = 188, 98.9%). The incidence of fibrosis in the paratracheal cyst group was 45.8% (n = 87) compared with 19.5% (n = 37) in the control group; this difference was statistically significant ( P < 0.001). The prevalence rates of emphysema in the cyst group and the control group were 29.5% (n = 56) and 11.6% (n = 22), respectively, and the difference was statistically significant ( P < 0.001). When the groups were compared regarding bronchiectasis (scar and non–scar related), the rate of bronchiectasis in the paratracheal cyst group was 17.9% (n = 34), compared with 3.7% (n = 7) in the control group; this difference was statistically significant ( P < 0.001). Conclusions: Paratracheal air cysts are relatively common, but the etiology is still unclear. We detected increased rates of cyst formation that may result from the traction effect on the tracheal wall in the presence of upper lobe fibrosis.